Analisis Potensi Lingkungan Kampus Sebagai Sumber Belajar Biologi - Hartono D. Mamu; Herinda Mardin (Peneliti.net, 2023)
The purpose of this research is to describe the benefits of the campus environment as a source of learning biology. So many learning difficulties experienced by students on campus. Utilization of various learning resources such as the campus environment is an effort to solve the problem of student learning difficulties. By learning directly in the natural environment, the learning experience experienced by students is more meaningful. Through direct learning in nature or the surrounding environment as a source of learning, it is able to make learning experiences concrete so that learning becomes optimal. The campus environment can be used as a learning resource for several relevant subjects. This research is a descriptive research from a literature study emphasizing the potential process analysis method of the environment around campus 4 of State University of Gorontalo as a source of learning biology. Campus 4 environment of Gorontalo State University, Bone Bolango Regency can be used as a learning resource in several subjects such as plant diversity, low-level and high-level plants, mycology, entomology and so on. This is due to the condition of the campus 4 environment of Gorontalo State University which is still beautiful and cool and has many tall and large trees, low-level plants that are still maintained, has many species of fungi and insects and so on.